1991
DOI: 10.2105/ajph.81.9.1192
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the fitness of fire fighters: the complex issues involved in abolishing mandatory retirement ages.

Abstract: IntoductonThe feasibility of abolishing mandatory retirement ages in public safety occupations is being studied under US congressional mandate. One suggestion has been to replace mandatory retirement ages with minimum standards for health and physical fitness.1 Before serious discussion regarding developing and implementing standards can begin, the impact of those standards on the current work force must be known. Therefore, we conducted a descriptive case study of a large municipal fire department (approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 9 publications
4
27
0
Order By: Relevance
“…A number of studies suggested that a firefighter should have V O2 max of at least 40 ml/min/kg [6,8,12,14,16,18,25,26,27,43,44]. Data in this study agree with the conclusion of former studies.…”
Section: O2 Maxsupporting
confidence: 90%
“…A number of studies suggested that a firefighter should have V O2 max of at least 40 ml/min/kg [6,8,12,14,16,18,25,26,27,43,44]. Data in this study agree with the conclusion of former studies.…”
Section: O2 Maxsupporting
confidence: 90%
“…Thus, the participants with V O2 max of 3-3.5 L/min (40-45 ml/min/kg) or less will not be able to complete the treadmill test and will not qualify to be smoke divers in Norwegian fire brigades. This minimum aerobic demand is in line with the suggested minimum standard of 40-45 ml/min/kg of other studies [1,2,3,7,11,12,13,14,15,16,17]. In their previous study, the authors of this paper suggested that to perform rescue work at a hospital, a male firefighter should have V O2 max of at least 4 L/min [5].…”
Section: Appropriate Tests and Requirementssupporting
confidence: 85%
“…Fire fighting, smoke diving and rescuing are presumably physically demanding, as reflected in high oxygen uptake (V O2 ) [1,2,3,4,5,6,7] and nearmaximum heart rate (HR) [8,9,10] during common fire fighting tasks. Firefighters' maximal oxygen uptake (V O2 max ) should be ~40 ml/min/kg or more [1,2,3,5,7,11,12,13,14,15,16,17]. Laboratory tests [18] and work-simulated tests [15,19,20] have been developed to ensure sufficient physical abilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data verify a deficit in functional capacity to perform necessary job-specific strenuous tasks, which typically worsens with advancing chronological age (6,54,60). Although the rate of decline is largely an individual phenomenon (31), further decrement may be attenuated with systematic screening and thorough exercise training (30).…”
Section: Discussionsupporting
confidence: 60%